2018
DOI: 10.33371/ijoc.v12i2.576
|View full text |Cite
|
Sign up to set email alerts
|

Expression of γ-H2AX Using Immunofluorescence Assay as an Adaptive Response of PBMC in Radiation Workers at Dharmais Cancer Hospital

Abstract: Background: Exposure ionizing of radiation in radiation workers has the potential to cause DNA damage in the form of double strand break as the beginning of genomic instability. DNA damage can be observed with γ-H2AX as the biomarker of DNA double strand breaks (DSBs). The formation of γ-H2AX in the nucleus can occur after radiation exposure of 1 mGy. This study aims to determine the radiation effects in radiation work environments as a study of adaptive responses of peripheral blood mononuclear cell (PBMCs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Previous research by Musthafa et al [7], which observed DNA damage in lymphocytes as an adaptive response in medical workers using the gamma H2AX method, showed no significant differences between the medical radiation workers group and the control group. Meanwhile, the results of micronuclei studies, apoptosis, and comet assay conducted by Mohammadi et al [18] stated that there might be a radioadaptive response in people living in high background areas in the Ramsar region, Iran.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…Previous research by Musthafa et al [7], which observed DNA damage in lymphocytes as an adaptive response in medical workers using the gamma H2AX method, showed no significant differences between the medical radiation workers group and the control group. Meanwhile, the results of micronuclei studies, apoptosis, and comet assay conducted by Mohammadi et al [18] stated that there might be a radioadaptive response in people living in high background areas in the Ramsar region, Iran.…”
Section: Introductionmentioning
confidence: 71%
“…In almost all research parameters, the MRW group had a higher average than the control group, except for TM (13.32±8.80 and 14.91±3.37; 15.89±13.59 and 22.55±5.63) and OTM (13.59±3.90 and 18.53±4.94; 14.75±1.67 and 23.63±3. 19) with radiation doses of 1.5 and 2 Gy. by immersion for 5 seconds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations